Dual Air-Conditioner Optimization : Intelligent Power Management Via Microcontroller - R. Thangasankaran; Dr. S. Parthasarathy; R. Hari Krishna; M. Jai Philbert; A. Dhanabalan (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This proposed paper presents an innovative IoT-based solution for automating dual air conditioner operation, leveraging ESP32 microcontrollers, temperature sensors, and Wi-Fi communication. The system continuously monitors room temperature and automatically switches the air conditioner on or off based on predefined thresholds. This real-time temperature monitoring and automation enhance comfort, save energy, increase system reliability, and reduce maintenance. The system optimizes AC operation, detects anomalies, and prevents power overloads, making it an efficient and safe solution for dual AC units. By employing inrush current testing, the system can accurately detect anomalies and prevent power overloads, enhancing both safety and energy efficiency. The proposed system is a compact, low-cost, and user-friendly solution that can be easily integrated into existing air conditioning systems. This project demonstrates the potential of IoT technology in improving energy efficiency and automation in various applications. The system's effectiveness is validated through experimental results, which show significant energy savings and improved system reliability. The project's findings have important implications for the development of smart buildings and cities.
Keywords: IoT; Air Conditioner; Automation; Energy Efficiency; ESP32 Microcontroller; Temperature Sensor; Wi-Fi Communication